2023
DOI: 10.1021/acsaem.3c00057
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of O2 Supply in Li–O2 Batteries with High and Low Doner Number Solvents

Abstract: The Li–O2 battery is a promising technology due to its high theoretical specific energy. However, its practical capacity and cycling performance need further improvement. In this scenario, the influence of the electrolyte and the supply of air/O2 to the device are essential to enhance the performance and build a commercial prototype. This paper presents a study focusing on the influence of oxygen flow and pressure in the gravimetric capacity of Li–O2 batteries using two different electrolytes: dimethyl sulfoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…While increasing the flow rate increased the capacity, very high flow rates had the opposite effect. Post-cycling analysis of the cell suggested that this was due to loss of electrolyte solution from the air electrode, which has been observed previously, 37,38 reconfirming the need for a solvent-management system. 34…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…While increasing the flow rate increased the capacity, very high flow rates had the opposite effect. Post-cycling analysis of the cell suggested that this was due to loss of electrolyte solution from the air electrode, which has been observed previously, 37,38 reconfirming the need for a solvent-management system. 34…”
Section: Resultssupporting
confidence: 75%
“…This will increase the need for saturation and capture of solvent from the gas stream. 37,38,45 For Li–air to become a commercially viable battery technology, we anticipate the need for a system-specific energy of >400 W h kg −1 . 3,33 Our calculations suggest that if a positive electrode capable of storing 40% vol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation